The education of medical librarians in Nigeria search for an appropriate programme - Afolayan, Olusegun Samuel O. (1983)
The education of medical librarians was explored from its beginning. It was found that while the special education exists and is desirable, there is no generally accepted standard in the following aspects of their education, namely: the qualifications of the candidates, the type and level of the programme, the subjects in the curriculum, the part to be played by library schools, and the role of the professional association of medical librarians. In view of these, this study was undertaken in order to discover a model that can be recommended to Nigerian library schools.